EMPLOYEESâ ORGANIZATIONAL COMMITMENT OF PROVINCIAL EDUCATION BOARD OF PROLIFERATION OF REGENCIES/CITIES IN RIAU PROVINCE (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThe purpose of this research is to knowing positif direct influence organizationalculture, motivation toward organizational commitment and organizational culturetoward motivation. The research approach kuantitatif method using survey and thenanalyzed by using with path analisys, to collage some data with quesioner. From thisresearch we can know positif direct influence: (1).organizational culture towardorganizational commitment, Ï31 = 0,232, r31 =0,612. (2) motivation towardcommitment organizational, Ï32 = 0,330, r32 =0,478. (3) organizational culture towardmotivation, Ï21 = 0,616, r21=0,827.. Implication result of this research is means toincrease Organizational Commitment of District Education Employees Organizational /City Expansion in Riau Province can rise with strengthen organizational culture andmotivation.Key-words: Organizational Culture, Motivation, Organizational Commitment